2021
DOI: 10.1167/iovs.62.9.36
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Transcriptomics Identifies a Unique Entity and Signature Markers of Transit-Amplifying Cells in Human Corneal Limbus

Abstract: PURPOSE. Differentiated from adult stem cells (ASCs), transit-amplifying cells (TACs) play an important role in tissue homeostasis, development, and regeneration. This study aimed to characterize the gene expression profile of a candidate TAC population in limbal basal epithelial cells using single-cell RNA sequencing (scRNA-seq). METHODS.Single cells isolated from the basal corneal limbus were subjected to scRNA-seq using the 10x Genomics platform. Cell types were clustered by graph-based visualization method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 58 publications
1
35
0
Order By: Relevance
“…Interestingly, primary limbal cells expressing a lower level amount of ΔNp63 and p63α, based on fluorescence intensity, also showed a reduced expression of caveolin-1 and cyclin-dependent kinase 2 respectively (Supplementary Figures S4 and S6 ). Interestingly, two recent studies also reported STMN1 and UBE2C to be specific markers of limbal transit amplifying cells 43 , 45 . Finally, in a 2019 single cell transcriptome study, Kaplan et al hypothesized that the stemness of mouse limbal epithelial stem cells could be regulated through autophagy 46 .…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, primary limbal cells expressing a lower level amount of ΔNp63 and p63α, based on fluorescence intensity, also showed a reduced expression of caveolin-1 and cyclin-dependent kinase 2 respectively (Supplementary Figures S4 and S6 ). Interestingly, two recent studies also reported STMN1 and UBE2C to be specific markers of limbal transit amplifying cells 43 , 45 . Finally, in a 2019 single cell transcriptome study, Kaplan et al hypothesized that the stemness of mouse limbal epithelial stem cells could be regulated through autophagy 46 .…”
Section: Discussionmentioning
confidence: 98%
“…Single-cell RNA-seq (scRNA-seq) technologies are broadly applied to dissect the cellular heterogeneity and expression dynamics, providing unprecedented insights into single-cell biology (Plass et al, 2018;Li et al, 2020). A few groups have recently used scRNA-seq to analyze LSC populations and corneal homeostasis (Li et al, 2021a;Li et al, 2021b). These data provide a new avenue for studying the mechanisms of LSC self-renewal (Altshuler et al, 2021).…”
Section: A Novel Strategy To Optimize Self-renewal and Expansion Of L...mentioning
confidence: 99%
“…Limbal TACs are considered to be ''early'' or immature due to their relatively undifferentiated phenotype, as opposed to ''late'' or mature central cornea TACs, which begin expressing corneal differentiation markers such as KRT12 (Kaplan et al, 2019;Lehrer et al, 1998). Recently, single-cell RNA sequencing (scRNA-seq) analyses of mixed corneal populations were performed and have begun to shed more light on corneal epithelial heterogeneity, including the LSC niche (Catala et al, 2021;Collin et al, 2021;Kaplan et al, 2019;Li et al, 2021).…”
Section: Introductionmentioning
confidence: 99%